2013
DOI: 10.3171/2013.3.jns121436
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of vasospasm-related morbidity and outcomes in patients with aneurysmal subarachnoid hemorrhage treated with clazosentan: a meta-analysis of randomized controlled trials

Abstract: Object Clazosentan therapy after aneurysmal subarachnoid hemorrhage (SAH) has been found to be effective in reducing the incidence of vasospasm in randomized controlled trials. However, while vasospasm-related morbidity, including delayed ischemic neurological deficits (DINDs) and delayed cerebral infarctions, was consistently decreased, statistical significance was not demonstrated and outcomes were not affected by clazosentan treatment. The objective of this meta-analysis was to determine whether clazosentan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Plenty of researches have focused on the cerebral vasospasm, which was traditionally deemed as the principal cause of poor prognosis in SAH patients [4][5][6][7][8][9]. Although animal experiments targeting post-SAH vasospasm and subsequent delayed ischemic neurological deficit (DIND) have reached promising results, it was not the same story recent clinical trials told [10][11][12]. Thus, other pathophysiology and mechanism involved in poor outcome after SAH was investigated, and early brain injury (EBI) which was defined as the process occurs within 72 h after SAH, has been proposed as a major cause of the poor outcomes following SAH [13][14][15][16].…”
Section: Introductionmentioning
confidence: 97%
“…Plenty of researches have focused on the cerebral vasospasm, which was traditionally deemed as the principal cause of poor prognosis in SAH patients [4][5][6][7][8][9]. Although animal experiments targeting post-SAH vasospasm and subsequent delayed ischemic neurological deficit (DIND) have reached promising results, it was not the same story recent clinical trials told [10][11][12]. Thus, other pathophysiology and mechanism involved in poor outcome after SAH was investigated, and early brain injury (EBI) which was defined as the process occurs within 72 h after SAH, has been proposed as a major cause of the poor outcomes following SAH [13][14][15][16].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, Phase III clinical trials in patients who had undergone treatment with placebo versus 5 mg/hour or 15 mg/hour of clazosentan demonstrated a significant reduction in vasospasm related morbidity and mortality at a dose of 15 mg/hour in a population of patients treated with endovascular coiling (CONSCIOUS-3) with no significant effect on neurological outcome, however, a similar study conducted in patients treated with surgical clipping showed no significant differences in vasospasm related morbidity and mortality following treatment with clazosentan at 5 mg/hour or 15 mg/ hour (CONSCIOUS-2) [33,34]. While these results are conflicting, a recent meta-analysis conducted by Shen et al including all four relevant trials demonstrated that treatment with clazosentan following aneurysmal SAH significantly reduces the incidence of vasospasm related DIND and delayed infarctions; however, this management does not improve neurological outcome [35]. Authors in this meta-analysis argued that this dissociation in results between the reduction of vasospasm related events and neurological outcomes can be explained by multiple factors, including that clazosentan is known to be effective on large vessels and its effect on the microvasculature is unknown, the causal relationship between vasospasm and poor outcome is weak, and poor outcome has many factors beyond vasospasm, including microthromboembolism, free radical injury, endothelial NO synthase dysfunction, and delayed neuronal injury.…”
Section: Vasospasmmentioning
confidence: 87%
“…In a study dealing with the prevention of vasospasm, Kawahara et al (19) recommended to perform early lumbar drainage in patients with SAH. In another study, it was reported that delayed ischemic neurological deficits decreased in patients treated with clazosentan (20). However, Velat et al Subarachnoid hemorrhage is a disease with a high mortality and morbidity.…”
Section: Discussionmentioning
confidence: 98%